Innovative capabilities: their drivers and effects on current and future performance - Lisboa, A. (2015)
This study investigates the role of a firm's orientation, both customer and competitor, in driving innovative capabilities and the impact of those capabilities on a firm's current and future performance. The study's contribution is threefold in that it (1) examines market-related exploitative and explorative capabilities in conjunction with product development exploitative and explorative capabilities in terms of their strategic drivers (firm orientation) and performance outcomes; (2) disentangles the effects of exploitative and explorative capabilities on current and future performance; and (3) examines the role of innovative capabilities within the particularly relevant, but understudied, context of exporting. The findings suggest that, although customer orientation relates to both exploitative and explorative capabilities, competitor orientation relates only to exploitative capabilities. Exploitative capabilities affect current performance, whereas explorative capabilities affect future performance. These findings are of crucial relevance to export managers in their quest to identify, extend, and create new market opportunities.